Conversion of levulinic acid to 2-butanone by acetoacetate decarboxylase from Clostridium acetobutylicum - Min, Kyoungseon; Kim, Seil; Yum, Taewoo; Kim, Yunje; Sang, Byoung-In; Um, Youngsoon (Springer Verlag, 2013)
In this study, a novel system for synthesis of 2-butanone from levulinic acid (gamma-keto-acid) via an enzymatic reaction was developed. Acetoacetate decarboxylase (AADC; E.C. 4.1.1.4) from Clostridium acetobutylicum was selected as a biocatalyst for decarboxylation of levulinic acid. The purified recombinant AADC from Escherichia coli successfully converted levulinic acid to 2-butanone with a conversion yield of 8.4-90.3 % depending on the amount of AADC under optimum conditions (30 A degrees C and pH 5.0) despite that acetoacetate, a beta-keto-acid, is a natural substrate of AADC. In order to improve the catalytic efficiency, an AADC-mediator system was tested using methyl viologen, methylene blue, azure B, zinc ion, and 2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) as mediators. Among them, methyl viologen showed the best performance, increasing the conversion yield up to 6.7-fold in comparison to that without methyl viologen. The results in this study are significant in the development of a renewable method for the synthesis of 2-butanone from biomass-derived chemical, levulinic acid, through enzymatic decarboxylation.